Mechanism for accurate, protein-assisted DNA annealing by Deinococcus radiodurans DdrB - Sugiman-Marangos, Seiji N. (Proc Natl Acad Sci U S A, 2016)
Accurate pairing of DNA strands is essential for repair of DNA double-strand breaks (DSBs). How cells achieve accurate annealing when large regions of single-strand DNA are unpaired has remained unclear despite many efforts focused on understanding proteins, which mediate this process. Here we report the crystal structure of a single-strand annealing protein [DdrB (DNA damage response B)] in complex with a partially annealed DNA intermediate to 2.2 Å. This structure and supporting biochemical data reveal a mechanism for accurate annealing involving DdrB-mediated proofreading of strand complementarity. DdrB promotes high-fidelity annealing by constraining specific bases from unauthorized association and only releases annealed duplex when bound strands are fully complementary. To our knowledge, this mechanism provides the first understanding for how cells achieve accurate, protein-assisted strand annealing under biological conditions that would otherwise favor misannealing.